Acoustic picture of starting screw compressors as a diagnostic parameter of technical condition - Pundik M.A.; Pichakhchi A.V.; Sidorov V.A. (Научно-технический вестник Брянского государственного университета)
The emergence of new opportunities for fixing and analyzing noise allows us to perform visualization and analysis of sound vibrations as diagnostic signs of the serviceability of the compression unit during the start-up period, the most informative stage of the manifestation of incipient damage. The use of screw compressors, at present, is the most rational due to the absence of shock processes, the possibility of long-term operation with a minimum amount of maintenance operations, the effective solution of issues of managing work schedules, minimal dynamic loads at startup, etc. Screw compressors with a frequency of rotation of the drive motor 3000 rpm and a power of 100…300 kW have found the greatest distribution. Ensuring long-term op-eration of screw compressors requires reasonable decision-making to restore operational capability on the basis of data on the actual condition of individual elements of the mechanism. The research methods are presented in the form of a practical analysis of the noise level and vibration acceleration of screw compressors. Acoustic and vibration parameters of the unit start-up were obtained, information frequencies of damage to the main nodes were presented, as well as a time-frequency spectrogram of the start-up. The results of the conducted acoustic studies of the start-up of the compressor unit consisting of Sabroe screw compressors SAB — 163 and SAB — 330 constitute the main content of this work, which allow us to conclude that it is necessary to implement three-level diagnostics of rotary mechanisms to prevent sudden failures of the compression unit.